Doctor Who. The day of the doctor [videorecording (DVD)] - Hurran, Nick; Moffat, Steven, 1961-; Baker, Tom, 1934-; Hurt, John, 1940-2017; Tennant, David, 1971-; Piper, Billie, 1982-; Smith, Matthew, 1988-; Coleman, Jenna, 1986- (2013)
The world's longest-running sci-fi series is celebrating its 50th anniversary with an explosive special. A celebration of Doctor Who unlike any other. "In 2013, something terrible is awakening in London's National Gallery; in 1562, a murderous plot is afoot in Elizabethan England; and somewhere in space an ancient battle reaches its devastating conclusion. All of reality is at stake as the Doctor's own dangerous past comes back to haunt him." -- Container.